ChemInform Abstract: Copper(I)‐Y Zeolite‐Catalyzed Regio‐ and Stereoselective [2 + 2 + 2] Cyclotrimerization Cascade: An Atom‐ and Step‐Economical Synthesis of Pyrimido[1, 6‐a]quinoline. Issue 9 (February 2016) - Ramanathan, Devenderan; Pitchumani, Kasi
Abstract: This regio‐ and stereoselective copper(I)‐Y zeolite‐catalyzed termolecular [2+2+2]/[NC+CC+NC] cycloaddition cascade reaction involves two molecules of the in situ generated N‐sulfonylketenimines and quinoline to afford functionalized pyrimidoquinolines.